Co-doped Sb2Te3 paramagnetic nanoplates. Issue 3 (21st December 2015) - Yang, Lei; Chen, Zhi-Gang; Nie, Tianxiao; Han, Guang; Zhang, Zhi; Hong, Min; Wang, Kang L.; Zou, Jin
Abstract : Paramagnetic Co-doped Sb2 Te3 nanoplates are fabricated using a facile and green solvothermal method. Abstract : Co-doped Sb2 Te3 nanoplates are fabricated using a facile and green solvothermal method. The as-synthesized nanoplates show uniform hexagonal morphology with a distribution of 1–2 μm in diameters and ∼50 nm in thickness. The detailed structural and compositional characterization indicates that Co uniformly distributes in Sb2 Te3 and leads to a lattice shrink of 1.22% along the a axis and 0.9% along the c axis. A Superconducting Quantum Interference Device magnetometer is used to determine the temperature dependent magnetization in zero-field cooled and field cooled processes. The paramagnetic state in our Co-doped Sb2 Te3 nanoplates is found from 5 K to 300 K.